Re-emergence of thiamine deficiency disease in the Pacific islands (2014-15): A case-control study. - Eric J Nilles; Atarota Manaia; Bineta Ruaia; Clare Huppatz; Catherine Ward; Peter George; Christiaan Sies; Alessio Cangiano; James Sejvar; André Reiffer; Teatoa Tira (PLoS ONE)
Background From late 2014 multiple atolls in Kiribati reported an unusual and sometimes fatal illness. We conducted an investigation to identify the etiology of the outbreak on the most severely affected atoll, Kuria, and identified thiamine deficiency disease as the cause. Thiamine deficiency disease has not been reported in the Pacific islands for >5 decades. We present the epidemiological, clinical, and laboratory findings of the investigation. Methodology/principal findings We initially conducted detailed interviews and examinations on previously identified cases to characterize the unknown illness and develop a case definition. Active and passive surveillance was then conducted to identify additional cases. A questionnaire to identify potential risk factors and blood samples to assay biochemical indices were collected from cases and asymptomatic controls. Thiamine hydrochloride treatment was implemented and the response to treatment was systematically monitored using a five-point visual analogue scale and by assessing resolution of previously abnormal neurological examination findings. Risk factors and biochemical results were assessed by univariate and multivariate analyses. 69 cases were identified on Kuria (7% attack rate) including 34 confirmed and 35 unconfirmed. Most were adults (median age 28 years [range 0-62]) and 83% were male. Seven adult males and two infants died (13% case fatality rate). Resolution of objective clinical signs (78%) or symptoms (94%) were identified within one week of starting treatment. Risk factors included having a friend with thiamine deficiency disease and drinking kava; drinking yeast alcohol reduced the risk of disease. Higher chromium (p<0·001) but not thiamine deficiency (p = 0·66) or other biochemical indices were associated with disease by univariate analyses. Chromium (p<0·001) and thiamine deficiency (p = 0·02) were associated with disease by multivariate analysis. Conclusions/significance An outbreak of thiamine deficiency disease (beriberi) in Kiribati signals the re-emergence of a classic nutritional disease in the Pacific islands after five decades. Although treatment is safe and effective, the underlying reason for the re-emergence remains unknown. Chromium was highly and positively correlated with disease in this study raising questions about the potential role of factors other than thiamine in the biochemistry and pathophysiology of clinical disease.